The Effectiveness of Group Counseling with Behavioral Contract Technique to Reduce Online Game Addiction of Students at SMA Negeri 1 Wuryantoro - Roshanda Meyla Fatihah; Mahmuddah Dewi Edmawati (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2025)
This research was conducted at SMA Negeri 1 Wuryantoro with the intention of finding out how good the behavioral contract strategy is in group counseling to reduce student addiction to online games. Pre-experimental research utilizing the One Group Posttest-Posttest Design paradigm was carried out. In this study, data was taken using purposive sampling design. Sampling strategies that consider certain criteria in harmony with the study vision are known as purposive sampling. Subjects with a very high and high level of internet game addiction are the targets in this study, because the sample strategy is intended to be utilized. Researchers use a non-parametric analytical test approach, namely the Wilcoxon Signed Rank test, to evaluate the efficacy of the services offered. By utilizing the data in the table, it can be concluded that group counseling with behavioral contract techniques is effective in reducing online game addiction in SMAN 1 Wuryantoro students, considering the z-calculation score of -2.021 and the significance value of 0.028 (<0.05). Therefore, we can test the hypothesis that online game addiction can be reduced effectively through group counseling.